Fabrication of fine features using digital light processing stereolithography - Chew, Ze Yong (2015)
Rapid prototyping technology has been popular in the recent decade due to the increasing adoption of mass customization, as well as process advantages such as short production lead time and satisfying product quality. However, rapid prototyping technologies are often costly and require laborious post processing steps. Thus, this project was developed with the objectives to: 1. reduce production cost of Stereolithography by optimizing low end commercial Stereolithography system – ASIGA Freeform Pico 39 Plus such that it is able to print fine features 2. explore effective and convenient post processing step such that it is able to reduce material wastage and at the same time further shorten production lead time The parameter study conducted revealed that every layer thickness has a specific optimal exposure time such that the layers could be printed just fine, with minimal compromise of the internal features’ accuracy. In addition, contrary to popular belief, light intensity did not have significant effect on the accuracy of internal features, though it was confirmed that a minimum light intensity is needed for proper printing. With the insights gained from parameter study, samples with high aspect ratio embedded cylindrical channels were successfully and consistently printed at the design diameter of 600 µm. On the other hand, the feasibility of centrifugation as a post process was studied and appropriate fixture was designed. Subsequent comparative experiment showed that centrifugation is as effective as conventional post processing steps, with the added bonus of close to 80% recovery of liquid resin and significant reduction in process time required.